Sociology of Students: A Theoretical Perspective and Research Practice - A. R. Tuzikov; R. I. Zinurova (Moscow Polytechnic University, 2019)
Higher school as a social institution aims at the formation of the most valuable resource of the XXI century that human capital is. Students are now an influential group of young people, and taking into consideration students' "advanced" status, its social activity (including network) and socio-political and socio-economic potential, we can assume that it is the student youth, which de- termines the youth "agenda". This makes constant research of students relevant and important, both at the theoretical and academic level of sociological science and at the level of applied knowledge focused on the constant monitoring of social well-being, lifestyle, values, opinions and activity of students in specific universities and in a whole country. Students are active participants of economic and social life; they have a significant political potential. The authors present the results of the monitoring of social well-being of first-year students at Kazan national research technological University. The method applied was a questionnaire study with the use of electronic resource. The article also dwells on the current state and trends of student studies, as well as the processes of their institutionalization. The authors emphasize the importance of sociological surveys of student life conducted with the help of student sociological labs.